Exploring Language Styles in Online Bedtime Stories for Children - Trioktaviani, Sindi; Degaf, Agwin (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
As essential knowledge tools, books appeal to a broad audience, including children, teenagers, and parents, with Bedtime Stories particularly captivating for children at night. This study examines the sociolinguistic characteristics of Bedtime Stories, emphasizing the variety of language styles used by authors to engage a child's imagination. Analyzing children's stories from online sources, focusing on five selected narratives, the researchers reveal a range of language styles - formal, informal, casual, and colloquial - with conversational style being the most prevalent. Additionally, this study identifies diverse language functions, including expressive, directive, referential, and phatic, with a significant emphasis on expressive functions. These insights extend our understanding of language use in bedtime stories and suggest directions for future research. Further studies should explore a broader and more varied sample, utilizing qualitative and quantitative methods, deepening our grasp of language styles in children's literature, particularly in the digital era. This exploration is crucial for comprehending how adaptable and diverse language styles can effectively engage children globally, fostering their cognitive and emotional development in our interconnected world.